P–804 Morphokinetic development by time-lapse imaging of conceptuses generated from artificial oocytes. (6th August 2021) - Trout, A; Xie, P; Petrini, A; Rosenwaks, Z; Palermo, G
Abstract: Study question: What are the ideal culture conditions to enhance full preimplantation development of embryos generated by FVB somatic cell haploidization (SCH) in the mouse model? Summary answer: The presence of a histone deacetylase inhibitor yielded the best morphokinetic development of expanded blastocysts generated by FVB SCH, comparable to control blastocysts. What is known already: Various culture conditions and medium supplements have been proposed to promote preimplantation development of embryos generated by SCH, including supplementation with trichostatin A (TSA), fasudil, scriptaid, and RAD–51 stimulatory compound–1 (RS–1). TSA and scriptaid, both histone-deacetylase inhibitors, have been found to improve embryo development following nuclear transfer by enhancing histone acetylation and cellular reprogramming. Additionally, fasudil is a Rho-associated kinase inhibitor that has been shown to reduce apoptosis and promote cell proliferation. Finally, RS–1 stimulates RAD51 activity, which promotes the repair of DNA damage and increases the efficacy of somatic cell reprogramming. Study design, size, duration: B6D2F1 mouse metaphase II (MII) oocytes underwent enucleation and nuclear transfer, or were ICSI inseminated serving as controls. Reconstituted oocytes showing development of a meiotic-like spindle demonstrated successful SCH, and were ICSI inseminated. SCH conceptuses were cultured in one of three groups: KSOM, KSOM supplemented with TSA (TSA), or KSOM supplemented with fasudil, scriptaid, and RS–1 (Cocktail). ICSI controls (ICSIC) were cultured in KSOM medium. Fertilization and full preimplantation development were compared among all groups. Participants/materials, setting, methods: Ooplasts were generated from MII oocytes by removing spindle complexes under OosightÔ visualization and cytochalasin B exposure. A single FVB mouse cumulus cell was transferred into the perivitelline space and fused with the ooplast, facilitated by Sendai virus. Reconstructed oocytes with novel pseudo-meiotic spindles underwent piezo-ICSI and were cultured in different media conditions in a time-lapse imaging system up to 96h. TSA and Cocktail embryos had media changed to regular KSOM 10 hours after insemination. Main results and the role of chance: A total of 274 B6D2F1 MII oocytes were enucleated, resulting in a 95.9% survival rate. All ooplasts survived nuclear transfer and 62.1% successfully haploidized after 2 hours. ICSIC and reconstituted SCH oocytes survived piezo-ICSI at rates of 81.5% and 57.0%, respectively (P < 0.01). SCH embryos were then allocated into KSOM, TSA supplied, and Cocktail media. Fertilization rates for ICSIC, KSOM, and TSA embryos were 92.4%, 90.7%, and 94.4%, respectively, while the rate for embryos cultured in Cocktail was only 71.9% (P < 0.03). While embryos cultured in Cocktail had a comparable 2-cell timing to ICSIC, embryos in TSA reached developmental milestones with a closer timing to the ICSIC, having minor delays at the 3-, 4-, and 6-cell stages (P < 0.05). KSOM- and Cocktail-cultured embryos were delayed at most of the stages (P < 0.01), except for the two-pronuclei appearance. Although the TSA group displayed the best embryo developmental pattern, the final rate of blastocyst development was somewhat homogeneous with rates of 15.4%, 23.5%, and 13.0% for the KSOM, TSA, and Cocktail groups, respectively (P < 0.001), and remarkably lower than the ICSIC (81.6%). Limitations, reasons for caution: Although live pups have been obtained using BDF cumulus cells, embryos generated by FVB cumulus cells show a remarkably lower blastocyst development, but maintain morphokinetic characteristics similar to ICSIC in the presence of TSA. Wider implications of the findings: While using different strains to enhance genetic variance, the morphokinetic analysis of preimplantation embryos in ideal culture conditions is paramount to the progress of neogametogenesis. The implementation of this technique may soon help create genotyped oocytes for women with compromised ovarian reserve. Trial registration number: N/A